Accountability Concept of Village Fund Management through Religious Spirit - Prasetio, Januar Eko; Sabihaini, Sabihaini (AIBPM Publisher, 2023)
Village funds management and its accountability reports in Indonesia are very important since it relates directly to many people in villages and deal with significant amount of funds. The accountability of village fund is also beneficial for the sustainability of the local government development. This study tries to deconstruct the accountability of the village funds using samples from eight villages in Tempel district, Sleman regency, Special Province of DI.Â Yogyakarta. The village heads, village secretaries, members of the village management board, and village treasurers were selected as the main informant.Â The validity of the data was done by several tests namely credibility, transferability, dependability, and confirmability tests. Results indicate that the accountability of village fund management in the observed sample sites covers vertical accountability, horizontal accountability, social accountability and spiritual accountability.Â This study imply that the ongoing accountability performed by the village fund managers is accountability in the perspective of both the world and the hereafter.